Optimization Study of the Solid Propellant (Rocket Fuel) Based on Extracted Bitumen of Indonesian Natural Buton Asphalt - Bardi Murachman; Sajono Sajono; Fauzan Afandi; Johan Khaeri (ASEAN Journal of Chemical Engineering, 2014)
The asphalt propellant for rockets has been investigated since 1960. This material has been developed with the variation of fuels, oxidizer, binders, metal elements and additives. As solid propellant, it has some advantages and disadvantages during the implementation. At present, Extracted Buton asphalt has been studied as an alternative propellant fuels. It is a natural asphalt, extracted from Buton island asphalt rock. When the extract of buton asphalt is mixed with oxidizer, binder, and metal powder, it can be functioned as propellant which is able to release high intensity of energy, have strong thrust and power to fly the rocket. This optimization study of solid propellant was conducted by mixing the Buton asphalt as fuel, oxidizer, metal element and other additives to form a solid propellant. The oxidizer consisted of potassium nitrate (KNO3) and potassium perchlorate (KClO4). The variations of KClO4/KNO3, propellant density and the ratio of the nozzle diameter were also conducted in order to find the best propellant composition and the optimum operating conditions to produce enough power while maintain the integrity of the rocket. The main parameters such as the propellant’s thrust (F) and the specific impulse (Isp) were examined. The results showed that higher composition of KClO4/KNO3 gave the higher value of the thrust and the specific impulse. KClO4/KNO3 levels above the 1:1 ratio produced an explosive properties at the time of ignition. The tendency of propellant to explode during ignition process was also observed. The optimum condition was obtained at the KClO4/KNO3 ratio of 1:1 , the propellant density was 1.900 gram/cm3 and Ae/A* was 3.33. These conditions generated impulse value that last for 277.07 seconds, average thrust of 14.082 N, and average rate of combustion of 0,24 cm/second. Therefore, it can be concluded that propellant with fuel from extracted of Buton asphalt can be used as an alternative propellant for rocket.